The Impact of Gender Composition of Boards on Firms Financial Performance in Poland - Jolanta Maj; Piotr Bebenek (Institute of Economic Research (IER), 2017)
The so far conducted studies have not been able to answer the question of whether there is a relationship between gender composition of the board and the firms financial performance. Because of the tendency to legally regulate the gender balance of boards of directors as it was, among others, planned in the draft of the EU Directive on improving the gender balance among non-executive directors of companies listed on stock exchanges, which admittedly has been rejected, however, indicates the existence of certain trends among decion-makers, the issue of determining the relationship between gender composition of the boards and firms performance becomes an extremely important issue. The paper aims to answer the question on the number of women in the highest organizational bodies in Polish enterprises and whether there is a relationship between the compositions of boards due to gender of their members and financial results achieved by the companies. For the analysis companies listed on the Warsaw Stock Exchange were analyzed. Following indicators: debt ratio (DR), debt to equity ratio (D/R) and the long-term debt to total assets ratio were chosen. Using statistical analysis the financial indicators were juxtaposed with the number of women on boards. The paper provides insight into the composition of boards in Polish companies listed on the Warsaw Stock Exchange due to gender. It shows that boards of these companies are highly masculine. Nevertheless the paper tries to show if there are any dependencies between the amount of women on boards and the financial performance of the companies.
Keywords: M14; M12; 330; gender diversity; corporate governance; board composition; firm performance; financial performance